The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1063/1.5121625
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced co-deformation of a heterogeneous nanolayered Cu/Ni composite

Abstract: Anomalous self-diffusion, structural and energy relaxations and temporal scaling laws in pure tantalum and pure vanadium metallic glasses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…The two findings indicate that the heterogeneous Cu/Ta NMMs shows a good deformation compatibility among the Cu and Ta layers during compression process. We note that the previous simulation studies by Wang et al [36] showed that a typical fcc/fcc heterogeneous nanolayered structure stacked by soft Cu and hard Ni layers also exhibit an excellent deformation compatibility between two materials under uniaxial compression.…”
Section: Deformation Mechanisms Of the Heterogeneousmentioning
confidence: 51%
See 2 more Smart Citations
“…The two findings indicate that the heterogeneous Cu/Ta NMMs shows a good deformation compatibility among the Cu and Ta layers during compression process. We note that the previous simulation studies by Wang et al [36] showed that a typical fcc/fcc heterogeneous nanolayered structure stacked by soft Cu and hard Ni layers also exhibit an excellent deformation compatibility between two materials under uniaxial compression.…”
Section: Deformation Mechanisms Of the Heterogeneousmentioning
confidence: 51%
“…After the relaxation, the heterogeneous Cu/Ta NMMs structures are subjected to elongation or compression at a constant strain rate. The strain rate is chosen as 1 × 10 9 s −1 , which is a commonly used value in previous simulation studies of NMMs structures [27,28,30,31,[34][35][36]. Figure 1(b) illustrates the loading directions, where the tensile loading is parallel to the Cu/Ta interfaces and along the X direction, while the compressive loading is perpendicular to the interface and along the Z axis.…”
Section: Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid development of modern industry has put forward higher requirements for the comprehensive performance of engineering metals. Many effective strategies have been proposed for improving the performance of engineering metals, such as microstructure optimization design 1 4 and alloying methods, 5 7 among which the alloying strategy commonly based on a single primary element has tended to be the bottleneck of performance. At the beginning of this century, a kind of novel alloying strategy based on several primary elements was proposed, which broke the limitations of traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of modern industry has put forward higher requirements for the comprehensive performance of engineering metals. Many effective strategies have been proposed for improving the performance of engineering metals, such as microstructure optimization design and alloying methods, among which the alloying strategy commonly based on a single primary element has tended to be the bottleneck of performance. At the beginning of this century, a kind of novel alloying strategy based on several primary elements was proposed, which broke the limitations of traditional methods. , The novel alloys are generally named as high/medium entropy alloys (HEAs/MEAs) because of their high configurational entropy, which often form compositionally complex solid solutions instead of intermetallic compounds. In the past years, HEAs have attracted more attention and interest due to their excellent properties and performances, especially mechanical properties, such as superior strength and hardness, outstanding fracture toughness and ductility, , and remarkable resistance to friction and wear …”
Section: Introductionmentioning
confidence: 99%